Kolaborasi Antara Orang Tua dan Guru dalam Model Pengasuhan Berbasis Pendidikan di PAUD - Afia, Sariah; Malik, Lina Revilla (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This research discusses the collaboration between parents and teachers in an education-based parenting model in early childhood education (PAUD), which plays a crucial role in supporting the holistic development of young children. Based on the literature review, collaboration that includes communication, parental participation, and support for learning at home positively impacts children's academic and social-emotional development. Teachers, with their professional competencies, act as facilitators who can design activities according to the developmental needs of children, while parents support learning through emotional stability and educational values at home. However, challenges such as differing perceptions, time limitations, and economic backgrounds require inclusive strategies, such as family-centered education models that position families as key partners in education. This approach has proven effective in enhancing children's motivation to learn and strengthening the emotional connections between children, parents, and teachers. In conclusion, harmonious collaboration can create a holistic and sustainable ecosystem.